Parents' Experience in Paud Hasan Basri, Cicurug District, Sukabumi Regency in Applying Discipline to Children Aged 5-6 Years - Syahidah, Alya Athifatu; Maulana, Redi Awal; Elnawati (Jurnal Indonesia Sosial Sains, 2025)
Discipline in early childhood is crucial for shaping children's behavior and character, yet parents face diverse challenges in applying effective discipline strategies. This study addresses the experiences of parents at Hasan Basri PAUD, Cicurug District, Sukabumi Regency, in disciplining children aged 5-6 years. The research aims to explore parents’ understanding of discipline, as well as the supporting and inhibiting factors affecting their implementation. Using a qualitative phenomenological approach, data were collected through in-depth interviews with parents to capture rich, contextual insights into their disciplinary practices. Data analysis was conducted using Interpretative Phenomenological Analysis (IPA) to identify emerging themes related to parental experience. The results reveal variation in discipline application: some parents successfully use consistent and positive methods such as positive reinforcement and structured daily routines, while others struggle with inconsistency, external stress, and resistance from children. Key supporting factors include parental knowledge, social support, and a stable home environment; major inhibiting factors include digital distractions and peer influence. The study highlights the importance of parent education and social support to promote effective discipline and child development. These findings contribute to the theoretical understanding of parenting discipline and provide practical insights for educators and policymakers to enhance early childhood education.